Structured Learning Approach Model (SLA) for Assertive Skills Training in Middle School Students - Djamaluddin, Mawardi; Canu, Zainab; Arifin, Asriyani M.; Sugianto, Hendi (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2020)
Communication and social skills are not yet wholly owned by students, so psychological problems often arise, for example, inability to convey wishes to others in a positive way, so that others often ignore matters relating to the rights of students. Therefore, students often place themselves as passive individuals when doing something that is fundamentally incompatible with their needs subjectively. This study aims to develop guidelines for assertive skills training to facilitate junior high school students to develop assertive skills. The research and development model used was adapted from Borg and Gall. Product development has gone through the stages of expert BK assessment and prospective product users. Data were collected using acceptability rating scale instruments. The data analysis technique used is the Inter-Rater Agreement Model. Based on the results of the study, it showed that the assertiveness skills training guide for junior high school students fulfilled the acceptability criteria, which included four aspects, namely the aspects of usefulness, feasibility, accuracy, and compliance.